Photonic Microwave Filter With Steep Skirt Selectivity Based on Stimulated Brillouin Scattering - Diego Samaniego; Borja Vidal (IEEE Photonics Journal, 2016)
A method to enhance the filter slope of Brillouin-based photonic microwave filters is presented. This improvement is achieved by the combination of Brillouin gain and loss responses over phase-modulated signals. The experimental results show passband responses exhibiting a slope of 16.7 dB per octave, which corresponds with a threefold improvement in comparison to the natural Lorentzian response for the same gain.